Neurotransmission and neuromodulation systems in the learning and memory network of Octopus vulgaris. (8th February 2022) - Stern‐Mentch, Naama; Bostwick, Gabrielle Winters; Belenky, Michael; Moroz, Leonid; Hochner, Binyamin
Abstract: The vertical lobe (VL) in the octopus brain plays an essential role in its sophisticated learning and memory. Early anatomical studies suggested that the VL is organized in a "fan‐out fan‐in" connectivity matrix comprising only three morphologically identified neuron types; input axons from the median superior frontal lobe (MSFL) innervating en passant millions of small amacrine interneurons (AMs), which converge sharply onto large VL output neurons (LNs). Recent physiological studies confirmed the feedforward excitatory connectivity; a glutamatergic synapse at the first MSFL‐to‐AM synaptic layer and a cholinergic AM‐to‐LNs synapse. MSFL‐to‐AMs synapses show a robust hippocampal‐like activity‐dependent long‐term potentiation (LTP) of transmitter release. 5‐HT, octopamine, dopamine and nitric oxide modulate short‐ and long‐term VL synaptic plasticity. Here, we present a comprehensive histolabeling study to better characterize the neural elements in the VL. We generally confirmed glutamatergic MSFLs and cholinergic AMs. Intense labeling for NOS activity in the AMs neurites were in‐line with the NO‐dependent presynaptic LTP mechanism at the MSFL‐to‐AM synapse. New discoveries here reveal more heterogeneity of the VL neurons than previously thought. GABAergic AMs suggest a subpopulation of inhibitory interneurons in the first input layer. Clear γ‐amino butyric acid labeling in the cell bodies of LNs supported an inhibitory VL output, yet the LNs co‐expressed FMRFamide‐like neuropeptides, suggesting an additional neuromodulatory role of the VL output. Furthermore, a group of LNs was glutamatergic. A new cluster of cells organized as a "deep nucleus" showed rich catecholaminergic labeling and may play a role in intrinsic neuromodulation. In‐situ hybridization and immunolabeling allowed characterization and localization of a rich array of neuropeptides and neuromodulators, likely involved in reward/punishment signals. This analysis of the fast transmission system, together with the newly found cellular elements, help integrate behavioral, physiological, pharmacological and connectome findings into a more comprehensive understanding of an efficient learning and memory network. Abstract : The vertical lobe in the brain of Octopus vulgaris is important for learning and memory and it demonstrates a robust activity‐dependent long‐term potentiation (LTP) as in the vertebrate hippocampus. This study uses various histological techniques to describe comprehensively the fast neurotransmitters and neuromodulators in the network and thus contribute to the understanding the function of the vertical lobe in the octopus learning.